Respuesta :

Louli
Answer:
The factored form is: (x-2)(x-4) = 0

Explanation:
To factor an expression, we need to get its solutions.

The standard form of the quadratic equation is:
ax² + bx + c = 0

The given equation is:
x² - 6x + 8 = 0

By comparison:
a = 1
b = -6
c = 8

Now, to get the roots, we will substitute with the values of a, b and c in the quadratic formula shown in the attached image.

This will give us:
either x = [tex] \frac{6+ \sqrt{(-6)^2-4(1)(8)} }{2(1)} = 4[/tex]
This means that the first factor is (x-4)

or x = [tex] \frac{6- \sqrt{(-6)^2-4(1)(8)} }{2(1)} = 2[/tex]
This means that the second factor is (x-2)

Based on the above, the factored form would be:
(x-4)(x-2) = 0

Hope this helps :)
Ver imagen Louli

Answer:

(x-2)(x-4)

Step-by-step explanation:

x^2 -6x +8

We need to find numbers that add to -6 but multiply  8. We know that 4 and 2 multiply to 8 but they do not add to -6. -4 and -2 add to -6 and -4 times -2 equal 8. Therefore the factored form of x^2 -6x + 8 is (x-2)(x-4).

Hope this helps:))) Hva e a good day